SeiP – Selbstinszenierungspraktiken als Zugang zu einer selbstbestimmten, multimodalen Kompetenzfeststellung für (aus-)bildungsbenachteiligte Jugendliche - Frehe-Halliwell, Petra; Kremer, H.-Hugo; Laubenstein, Désirée; Kundisch, Heike; Otto, Franziska; Seib, Jessica; Geisler, Tobias (Förderbezogene Diagnostik in der inklusiven Bildung. Professionalisierung – spezifische Unterstützungsangebote – Übergänge in die berufliche Bildung)
Die Umsetzung eines inklusiven Bildungssystems stellt nach wie vor eine große Herausforderung für die Bildungspolitik, Bildungsverwaltung und Bildungspraxis dar. Das BMBF reagierte darauf mit der Schwerpunktsetzung auf inklusive Bildung im Kontext des Rahmenprogramms ›Empirische Bildungsforschung‹. In den beiden Sammelbänden werden die Ergebnisse der zweiten Förderlinie, welche den Fokus auf ›Förderbezogene Diagnostik‹ setzt, vorgestellt. Sie ermöglichen einer breiten Leserschaft aus Bildungspraxis, Bildungsverwaltung, Bildungspolitik und Bildungsforschung, sich einen raschen Überblick über die Zielsetzungen, die Vorgehensweise und die Ergebnisse der 28 im Rahmen dieses Programms geförderten Projekte zu verschaffen. Dieser Band befasst sich mit überfachlichen Aspekten, und zwar mit der Praxis der Diagnostik, der Professionalisierung der pädagogischen Fachkräfte, den Unterstützungsangeboten sowie den Übergängen in die berufliche Bildung.

Selbstinszenierungspraktiken als Zugang zu einer selbstbestimmten, multimodalen Kompetenzfeststellung für (aus-)bildungsbenachteiligte Jugendliche: Entwicklungsansatz, SeiP-Rahmenkonzept und exemplarische Methoden. - Frehe-Halliwell, Petra; Kremer, H.-Hugo; Otto, Franziska (Didaktik in der Ausbildungsvorbereitung. Selbstinszenierungspraktiken als subjektorientierter Zugang (aus-)bildungsbenachteiligter Jugendlicher)

Selbstinszenierungspraktiken als Zugang zu einer selbstbestimmten, multimodalen Kompetenzfeststellung für (aus-)bildungsbenachteiligte Jugendliche (SeiP) - Frehe-Halliwell, Petra; Kremer, H.-Hugo; Kundisch, Heike; Otto, Franziska; Laubenstein, Désirée; Seib, Jessica (Didaktik in der Ausbildungsvorbereitung. Selbstinszenierungspraktiken als subjektorientierter Zugang (aus-)bildungsbenachteiligter Jugendlicher)

Selbstinszenierung als Zugang zum Selbstkonzept – Theoretisch-konzeptionelle Annäherungen und Überlegungen zur didaktischen Gestaltung - Otto, Franziska; Kremer, H.-Hugo (Didaktik in der Ausbildungsvorbereitung. Selbstinszenierungspraktiken als subjektorientierter Zugang (aus-)bildungsbenachteiligter Jugendlicher)

Entdeckungsräume: Eröffnen – Eintauchen – Mitgehen. Zur Konturierung einer subjektorientierten Didaktik in der Ausbildungsvorbereitung - Frehe-Halliwell, Petra; Kückmann, Marie-Ann; Otto, Franziska (bwp@ Profil 12: Transformationen in der beruflichen Bildung – Handlungsräume und Gestaltungsfelder der Wirt-schafts- und Berufspädagogik. Digitale Festschrift für H.-Hugo Kremer zum 60. Geburtstag)

Handreichung: Zum starken Selbst im Übergang Schule–Beruf! : Materialien und Umsetzungsbeispiele aus dem Forschungs- und Entwicklungsprojekt "SeiP": Selbstinszenierungspraktiken als Zugang zu einer selbstbestimmten, multimodalen Kompetenzfeststellung für (aus-) bildungsbenachteiligte Jugendliche - Otto, Franziska; Frehe-Halliwell, Petra; Kremer, H.-Hugo; Kundisch, Heike

Selbsterkundung und Selbstinszenierung: Potenziale entfalten. Übergänge gestalten - Kremer, H.-Hugo; Otto, Franziska (BVkE-Info)

Brexit and European Corporate Bond Markets - Franke, Benedikt; Kosi, Urska; Stoczek, Pia
We investigate the impact of Brexit on the corporate bond market by analyzing a comprehensive database covering corporate bond listings on European and UK trading venues. We find a significant shift in bond market activity, evidenced by a 49% increase in the number of bond listings in the EEA30 countries relative to the UK market after Brexit. Country-level analyses reveal a staggered effect on market activity, with predominantly international issuers adjusting their bond listings between the initially scheduled Brexit date and the final withdrawal date. At the issuer level, our findings indicate that the relative attractiveness of the EEA30 market has increased post-Brexit. Overall, these results suggest that the European capital market has successfully adapted to the loss of its largest financial center and exhibits a rising corporate bond market activity.

Abschreibungen als Mittel der Investitionsförderung in Deutschland - Möglichkeiten, Grenzen und Perspektiven evidenzbasierter Analysen - Dyck, Daniel; Hechtner, Frank; Maiterth, Ralf; Sureth-Sloane, Caren (Steuer und Wirtschaft)

On Chamber-regular C̃₂-Lattices - Stamer, Franziska; Titz Mite, Thomas
We construct the first examples of chamber-regular lattices on C̃₂-buildings. Assuming a conjecture of Kantor our list of examples becomes a classification for chamber-regular C̃₂-lattices on locally-finite C̃₂-buildings. The links of special vertices in the buildings we construct, are all isomorphic to (the incidence graph of) the unique generalized quadrangle Q of order (3,5). In particular our constructions involve chamber-regular actions on Q. These actions on Q are the first (and if Kantor's conjecture holds the only) chamber-regular actions on a finite generalized quadrangle and therefore interesting in their own right. Moreover Q is not Moufang and therefore none of our examples is a Bruhat-Tits building and all our lattices are exotic building lattices.

Von der Idee zur Umsetzung – Der Schulversuch an der Maria-Montessori-Gesamtschule in Düsseldorf - Schmitt-Richter, Lena Katharina; Wüllner, Sabrina; Schmidt, Katharina; Ebeling, Muna (PädagogikUNTERRICHT. Die Fachzeitschrift für die pädagogische Fächergruppe.)

Out of Order: On the Importance of Word Positions in Explaining Text Classification - Lütke Stockdiek, Janina; Grimme, Britta; Griesbach, Marie; Grimme, Christian (International Artificial Intelligence Symposium)

Are the differences not that different? Exploring an age perspective on employee preferences using an employer review platform - Lauterbach, Ann Sophie; Radermacher, Katharina (German Journal of Human Resource Management: Zeitschrift für Personalforschung)
Due to demographic changes and their impact on the labor market, attracting and retaining older employees plays a decisive role in organizations’ ability to maintain their workforce. This requires organizations to publicly display a work environment that fits the particular preferences of this target group. Drawing on lifespan theories, we examine how the link between employee preferences and employees’ likelihood of recommending their employer to others varies by age. To address the lack of integration between the literatures on workforce aging and employer branding, we take an empirical approach analyzing 292,429 numeric and unedited text-based employee reviews from an employer rating platform. Our findings reveal that relationship-building, fair and appreciative supervisor behavior, positive interactions with older colleagues, and location-flexible, efficient working conditions play pivotal roles in shaping older employees’ likelihood of recommending their employer. Although these age-related interaction effects are significant, they remain small, suggesting broadly compatible preferences between older and younger employees. We also demonstrate that these findings are robust across gender and different income groups. Finally, we provide tangible recommendations for the incorporation of lifespan theories in the employer branding context and highlight the value of using platform data for future research.

Positionspapier: Bildung für nachhaltige Entwicklung (BNE) in der Lehrkräftebildung an der UPB - Fechner, Sabine; Schlegel-Matthies, Kirsten; Kiepe, Karina

Transformation der deutschen Wirtschaft im Kontext nachhaltiger Entwicklung - Zur Rolle von Berufsbildung und ihrer Akteure - Krause, Ina; Kiepe, Karina (Ökonomie und Gesellschaft Jahrbuch 37: Nachhaltigkeit und soziale Gerechtigkeit)

L p Asymptotics for the Heat Equation on Symmetric Spaces for Non-symmetric Solutions - Papageorgiou, Efthymia (International Mathematics Research Notices)
Abstract The main goal of this work is to study the $L^{p}$-asymptotic behavior of solutions to the heat equation on arbitrary rank Riemannian symmetric spaces of non-compact-type $G/K$ for non-bi-$K$ invariant initial data. For initial data $u_{0}$ compactly supported or in a weighted $L^{1}(G/K)$ space with a weight depending on $p\in [1, \infty ]$, we introduce a mass function $M_{p}(u_{0})(\cdot )$, and prove that if $h_{t}$ is the heat kernel on $G/K$, then $$ \begin{align*} &\|h_t\|_p^{-1}\,\|u_0\ast h_t \, - \,M_p(u_0)(\cdot)\,h_t\|_p \rightarrow 0 \quad \textrm{as} \quad t\rightarrow \infty.\end{align*} $$ Interestingly, the $L^{p}$ heat concentration leads to completely different expressions of the mass function for $1\leq p <2$ and $2\leq p\leq \infty $. If we further assume that the initial data are bi-$K$-invariant, then our mass function boils down to the constant $\int _{G/K}u_{0}$ in the case $p=1$, and more generally to $\mathcal{H}{u_{0}}(i\rho (2/p-1))$ if $1\leq p<2$, and to $\mathcal{H}{u_{0}}(0)$ if $2\leq p \leq \infty $. Thus, we improve upon results by Vázquez, Anker et al., and Naik et al., clarifying the nature of the problem.

Blow-up exponents and a semilinear elliptic equation for the fractional Laplacian on hyperbolic spaces - Bruno, Tommaso; Papageorgiou, Efthymia (arXiv:2509.12349)
Let $\mathbb{H}^n$ be the $n$-dimensional real hyperbolic space, $Δ$ its nonnegative Laplace--Beltrami operator whose bottom of the spectrum we denote by $λ_{0}$, and $σ\in (0,1)$. The aim of this paper is twofold. On the one hand, we determine the Fujita exponent for the fractional heat equation \[\partial_{t} u + Δ^σu = e^{βt}|u|^{γ-1}u,\] by proving that nontrivial positive global solutions exist if and only if $γ\geq 1 + β/ λ_{0}^σ$. On the other hand, we prove the existence of non-negative, bounded and finite energy solutions of the semilinear fractional elliptic equation \[ Δ^σ v - λ^σ v - v^γ=0 \] for $0\leq λ\leq λ_{0}$ and $1<γ< \frac{n+2σ}{n-2σ}$. The two problems are known to be connected and the latter, aside from its independent interest, is actually instrumental to the former. \smallskip At the core of our results stands a novel fractional Poincaré-type inequality expressed in terms of a new scale of $L^{2}$ fractional Sobolev spaces, which sharpens those known so far, and which holds more generally on Riemannian symmetric spaces of non-compact type. We also establish an associated Rellich--Kondrachov-like compact embedding theorem for radial functions, along with other related properties.

Freudig in die Schlacht - Emotionen als Codes für die recta intentio im gerechten Krieg (8.- 10. Jahrhundert) - Foerster, Anne (Emotionen im Krieg - Krieg der Emotionen)

Co-Designing NVM-based Systems for Machine Learning and In-memory Search Applications - Henkel, Jörg; Siddhu, Lokesh; Nassar, Hassan; Bauer, Lars; Chen, Jian-Jia; Hakert, Christian; Seidl, Tristan; Chen, Kuan Hsun; Hu, Xiaobo Sharon; Li, Mengyuan; Yang, Chia-Lin; Wei, Ming-Liang (Proceedings of the 43rd IEEE/ACM International Conference on Computer-Aided Design)

InTreeger: An End-to-End Framework for Integer-Only Decision Tree Inference